2016
DOI: 10.54652/rsf.2016.v46.i2.71
|View full text |Cite
|
Sign up to set email alerts
|

CONTRIBUTION TO MOLECULAR GENETIC CHARACTERIZATION OF HELLEBORUS MULTIFIDUS Vis. IN BOSNIA AND HERZEGOVINA

Abstract: UDK: 582.675.1:575(497.6) Helleborus multifidus Vis. is endemic Illyric-Adriatic species with distribution range in Italy, Slovenia, Croatia, Bosnia and Herzegovina, Montenegro and Albania. Although few studies reported different taxonomic categories for H. multifidus, this one is the first using molecular-genetic markers (trnL region and matK of chloroplast DNA and nuclear ITS1 and ITS2 region) for genetic characterization of H. multifidus presented at three localites in Bosnia and Herzegovina. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Lasić et al [31] used molecular genetic markers (trnL region and matK of chloroplast DNA and nuclear ITS1 and ITS2 region) to genetically characterize H. multifidus in three localities in Bosnia and Herzegovina. The results showed differences between the populations from Herzegovina and Bosnia, and indicated that the two populations did not belong to the same taxon.…”
Section: Analysis Of Phylogenetic Relationships By Molecular Techniquementioning
confidence: 99%
“…Lasić et al [31] used molecular genetic markers (trnL region and matK of chloroplast DNA and nuclear ITS1 and ITS2 region) to genetically characterize H. multifidus in three localities in Bosnia and Herzegovina. The results showed differences between the populations from Herzegovina and Bosnia, and indicated that the two populations did not belong to the same taxon.…”
Section: Analysis Of Phylogenetic Relationships By Molecular Techniquementioning
confidence: 99%
“…В связи с этим, необходим постоянный мониторинг генетического потенциала редких и исчезающих видов растений. Среди мер, которые в первую очередь должны быть включены, это мониторинг анализа внутрипопуляционного полиморфизма, генетическая дифференциация популяций, а также изучение морфологии видов и биологическая характеристика популяций [19,24].…”
unclassified